The rational investigation of bimetallic selenides as electrode materials for hybrid supercapacitors. (20th August 2022) - Garlapati, Kiran Kumar; Nath, Anish R.; Arjun, Ajith Mohan; Vijayan, Aruna; Sandhyarani, N.
Abstract: Cobalt is an ideal material for application in energy storage devices owing to its superior stability and redox activity. However, there has been a rise in demand for cobalt-based energy storage devices, which cannot be satisfied because of cost considerations. To balance demand and cost, cost-effective alternatives like copper can be envisaged. The present work underlines the potential of nickel-copper selenide as a suitable replacement for nickel-cobalt selenide electrodes for hybrid supercapacitor (HSCs) application. In half cell testing, NiCuSe and NiCoSe deliver a specific capacity of 127.2 mAh g −1 and 177.2 mAh g −1, respectively, at a current density of 3 A g −1 . NiCuSe exhibits more stable charge storage than NiCoSe at high current densities owing to its superior conductivity. Aqueous HSCs, NiCuSe// modified activated carbon (MAC) and NiCoSe//MAC deliver an energy density and power density of 26.56 Wh kg −1 at 2.732 kW kg −1 and 28.78 Wh kg −1 and 2.571 kW kg −1, respectively. NiCuSe//MAC shows superior rate capability, and both devices exhibit superior cycle life for 12, 000 cycles. Graphical abstract: Image, graphical abstract .